Assessment of Training of Agents of the Prison System at Ceará State in Youth and Adults Education - Wagner Bandeira Andriola (Universidad Autónoma de Madrid, 2016)
The text brings up discussion about the relevance of training for the prison system in the area of youth and adults education. Under this view, presents the results of a systematic evaluation of improvement in EJA, for 300 agents of the prison system of Ceará, focusing on the processes and products. From the application of questionnaires to the 300 agents, it was found that there was excellence in performance of teachers in educational management, the physical infrastructure of the school, in curriculum content and addressed the relevance of these for the use professional and citizen of agents of the prison system.